A non-noble material cathode catalyst dual-doped with sulfur and nitrogen as efficient electrocatalysts for oxygen reduction reaction. (20th September 2015) - Xu, Li; Pan, Guoshun; Shi, Xiaolei; Zou, Chunli; Zhou, Yan; Luo, Guihai; Chen, Gaopan
Abstract: The behavior of Fe-based dual-doped non-noble metal electrocatalyst (Fe-N/C-TsOH) pyrolyzed at different condition and the repercussion for the oxygen reduction reaction (ORR) has been studied. Cyclic voltammetry (CV) and rotating disk electrode (RDE) with Tafel theory as well as Koutecky-Levich were used to quantitatively obtain the oxygen reduction reaction (ORR) kinetic constants and the reaction mechanisms. The pyrolyzed catalysts showed significantly improved ORR activity as well as different ORR mechanism, indicating that heat-treatment is a necessary step for improving catalyst activity. In addition, the optimal heat-treatment temperature was found to be 600 °C, and the overall ORR electron transfer numbers were found to be about 3.899, suggesting that the ORR catalyzed by Fe-N/C-TsOH-600 is a 4-electron transfer process from O2 to H2 O. Furthermore, the catalysts also have been subjected to chemical treatments in 0.5 mol·L −1 H2 SO4 to remove impurities and reheating was emplyed to optimize the electrocatalytic activity of the catalyst towards the ORR in alkaline medium. And the activity of the catalyst for the ORR increases obviously after H2 SO4 leaching and reheating. This effect account to the removal of impurities and purify the active sites as well as the factor that increase the amount of smaller pores which can provide a large surface area and expose more ORR-relevant active sites. In order to understand the heat-treatmen effect on catalyst, X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) are employed to detect surface structure changes. The results revealed a fact that the temperature of thermal treatment has a direct influence on crystal structure and compositions of the catalysts.